Structure and Conservation of Amyloid Spines From the Candida albicans Als5 Adhesin - Golan, Nimrod; Schwartz-Perov, Sergei; Landau, Meytal; Lipke, Peter N. (Frontiers in Molecular Biosciences, 2022)
Candida Als family adhesins mediate adhesion to biological and abiotic substrates, as well as fungal cell aggregation, fungal-bacterial co-aggregation and biofilm formation. The activity of at least two family members, Als5 and Als1, is dependent on amyloid-like protein aggregation that is initiated by shear force. Each Als adhesin has a ~300-residue N-terminal Ig-like/invasin region. The following 108-residue, low complexity, threonine-rich (T) domain unfolds under shear force to expose a critical amyloid-forming segment 322SNGIVIVATTRTV334 at the interface between the Ig-like/invasin domain 2 and the T domain of Candida albicans Als5. Amyloid prediction programs identified six potential amyloidogenic sequences in the Ig-like/invasin region and three others in the T domain of C. albicans Als5. Peptides derived from four of these sequences formed fibrils that bound thioflavin T, the amyloid indicator dye, and three of these revealed atomic-resolution structures of cross- spines. These are the first atomic-level structures for fungal adhesins. One of these segments, from the T domain, revealed kinked -sheets, similarly to LARKS (Low-complexity, Amyloid-like, Reversible, Kinked segments) found in human functional amyloids. Based on the cross- structures in Als proteins, we use evolutionary arguments to identify functional amyloidogenic sequences in other fungal adhesins, including adhesins from Candida auris. Thus, cross- structures are often involved in fungal pathogenesis and potentially in antifungal therapy.